2005
DOI: 10.1111/j.1600-0846.2005.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of asymmetric blotches (asymmetric structureless areas) in dermoscopy images of malignant melanoma using relative color

Abstract: Neural network and statistical analysis showed that the blotch detection method was somewhat more effective using relative color than using absolute color. The relative-color blotch detection method gave a diagnostic accuracy of about 77%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Third, relative color is more natural from a perceptual point of view. Recent studies 10,11 have confirmed the usefulness of relative color features in skin lesion image analysis. ; ; ;…”
Section: Relative Color Featuresmentioning
confidence: 82%
See 1 more Smart Citation
“…Third, relative color is more natural from a perceptual point of view. Recent studies 10,11 have confirmed the usefulness of relative color features in skin lesion image analysis. ; ; ;…”
Section: Relative Color Featuresmentioning
confidence: 82%
“…However, feature extraction in dermoscopy images is relatively unexplored. The dermoscopic feature extraction studies to date include two pilot studies on pigment networks 21,22 and globules 21 , and three systematic studies on dots 23 and blotches 11,24 . To the best of our knowledge, there is no published systematic study on the detection of blue-white veil.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the papers present one approach to cover one or some of the "letters" of the rule, that is, some are based on detecting asymmetry [7,8], borders [9][10][11][12], colour [13][14][15] or diameter [14]. There are some papers that cover the whole ABCD criterion.…”
Section: Introductionmentioning
confidence: 98%
“…Blotches that are located asymmetrically within a lesion are indicative of malignant melanoma. Image processing techniques have been developed to find blotches automatically [3,4]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…al. [3] can be divided into two categories. The first employed absolute color thresholding for segmenting blotch-like regions, wherein threshold values were placed on the red, green, and blue (RGB) color planes in the digital images of skin lesions.…”
Section: Introductionmentioning
confidence: 99%